2019
DOI: 10.1111/jonm.12848
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sense of coherence, health and work engagement among nurses

Abstract: Aim To examine the sense of coherence among registered nurses and its relationship with health and work engagement. Background Sense of coherence is a global orientation to view life as structured, manageable and meaningful and have the capacity to cope with stressful situations. A high sense of coherence score indicates that an individual can understand, manage and attribute meaning to events in his or her life as well as in the work environment. Registered nurses face many workplace stressors that may be eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 44 publications
(73 reference statements)
8
34
1
4
Order By: Relevance
“…On the other hand, the participants in this study showed a high SOC, similar to the scores found in previous studies [43]. High levels of SOC among healthcare professionals have been associated with better health status, more work engagement, and fewer work-related family conflicts [44]. A negative association between SOC and stress has also been identified among midwives [45].…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, the participants in this study showed a high SOC, similar to the scores found in previous studies [43]. High levels of SOC among healthcare professionals have been associated with better health status, more work engagement, and fewer work-related family conflicts [44]. A negative association between SOC and stress has also been identified among midwives [45].…”
Section: Discussionsupporting
confidence: 87%
“…The most valued WE dimension was dedication, as in the study by Mason et al (2014). The strong SOC manifested by the participants of this study resembles that described in similar previous studies such as the one by Malagon-Aguilera et al (2019) with a SOC = 67.9 (10.2) or Eriksson et al, (2019) with SOC = 61.43 (0.76). Authors such as Ando and Kawano (2018) agreed that the most valued SOC dimension is meaningfulness, as revealed in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Maintaining the psycho-emotional well-being of frontline health workers and building up their resilience are crucial in addressing and containing COVID-19 (Chen et al, 2020). In this sense, Work Engagement (WE) and Sense of Coherence (SOC) are two competencies that can help professionals cope with work-related psychological distress (PD) and contribute to their well-being and health (Malagon-Aguilera et al, 2019). Schaufeli et al (2002) described WE as a positive and satisfying attitude related to work that is characterized by vigour, dedication and absorption.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study relative to the long-term care environment reinforced the importance of leaders providing positive and empowering guidance, setting up systems to support team members, providing robust orientation and training on the specific needs of the medically complex population, and reinforcing the positive aspects both in the staff and in the environment, consistent with literature and findings in hospital and healthcare systems [7][8][9][10][11][12][13][14][15]. Supportive leadership was the most cited, influential, and positive facilitator in long-term care settings, along with setting up systems, processes, and tools to better support associates [22,23,25,29,30,34,41,45,47,[65][66][67][68], setting a positive culture [22][23][24]29,[31][32][33]48,51,53,54,57,[60][61][62][63][64], and inspiring employees [22,26,30,32,35,…”
Section: Organizational Leadershipsupporting
confidence: 78%
“…The 162 occurrences were grouped into 11 different themes for the facilitators. The eleven "facilitator" themes as demonstrated in Table 2 and represented in Figure 1 included supportive leadership , capable and motivated employees [22,27,30,32,35,45,[49][50][51][52][53][54][55][56][57][58][59][60], positive organizational values [22][23][24]29,[31][32][33]48,51,53,54,57,[61][62][63][64], social support mechanisms, adequate job resources [32,38,45,47,54,55,[69][70][71], career/professional development [25,35,37,38,…”
Section: Most Impactful Themesmentioning
confidence: 99%